An experimental study of ascorbic acid effects in acute renal failure under general anesthesia - Ozturk,Omur (2017)
Abstract Purpose: To evaluate the preventive effect of ascorbic acid on sevoflurane-induced acute renal failure in an experimental rat model. Methods: Twenty-four adult male Wistar rats were randomly distributed into three groups. Subjects were allocated into 3 groups: Group I received sevoflurane only, whereas Groups II and III had moderate (150 mg/kg) and high (300 mg/kg) doses of AA in addition to sevoflurane, respectively. Rhabdomyolysis and myohemoglobinuric ARF was formed by intramuscular administration of glycerol on the upper hind limb on the 15th minute of inhalation anesthesia. Biochemical parameters consisted of serum levels of blood urea nitrogen, creatinine, neutrophil gelatinase-associated lipocalin (NGAL), total antioxidant capacity (TAC), and protein carbonyl content. Histopathological variables were tubular necrosis, fibrin, and cast formation. Results: NGAL levels were significantly lower in Group III than Group II and Group I. On the other hand, TAC, PCO, urea and creatinine levels were notably higher in Group I compared with Groups II and III. There was a significant difference between 3 groups on frequencies of acute tubular necrosis (p=0.003), fibrin (p<0.001) and cast (p<0.001). Acute tubular necrosis and fibrin formation were more prominent in Group I. Casts were more common in Groups II and III. Conclusions: The ascorbic acid serve as a prophylactic agent against renal damage in patients receiving sevoflurane anesthesia and higher doses were associated with more apparent protective effects.